Genetic assortative mating for schizophrenia and bipolar disorder. Issue 1 (23rd August 2022) - Jefsen, Oskar Hougaard; Nudel, Ron; Wang, Yunpeng; Bybjerg-Grauholm, Jonas; Hemager, Nicoline; Christiani, Camilla A. J.; Burton, Birgitte K.; Spang, Katrine S.; Ellersgaard, Ditte; Gantriis, Ditte L.; Plessen, Kerstin Jessica; Jepsen, Jens Richardt M.; et al.
Abstract: Background: Psychiatric disorders are highly polygenic and show patterns of partner resemblance. Partner resemblance has direct population-level genetic implications if it is caused by assortative mating, but not if it is caused by convergence or social homogamy. Using genetics may help distinguish these different mechanisms. Here, we investigated whether partner resemblance for schizophrenia and bipolar disorder is influenced by assortative mating using polygenic risk scores (PRSs). Methods: PRSs from The Danish High-Risk and Resilience Study—VIA 7 were compared between parents in three subsamples: population-based control parent pairs ( N =198), parent pairs where at least one parent had schizophrenia ( N =193), and parent pairs where at least one parent had bipolar disorder ( N =115). Results: The PRS for schizophrenia was predictive of schizophrenia in the full sample and showed a significant correlation between parent pairs ( r =0.121, p =0.0440), indicative of assortative mating. The PRS for bipolar disorder was also correlated between parent pairs ( r =0.162, p =0.0067), but it was not predictive of bipolar disorder in the full sample, limiting the interpretation. Conclusions: Our study provides genetic evidence for assortative mating for schizophrenia, with important implications for our understanding of the genetics of schizophrenia.